Digital WebGIS Transformation for Strategic Tsunami Mitigation Management in Rajabasa District - Rasyid, Fachri Muhammad; Jamaludin, Jamaludin (Technomedia Journal, 2026)
This study examines land-use suitability and tsunami disaster mitigation in Rajabasa District, one of the areas most severely affected by the 2018 Sunda Strait tsunami. Indonesia’s high coastal disaster exposure underscores the urgency of integrating spatial planning with risk reduction. Using a quantitative-descriptive spatial approach, this research assesses the conformity between existing land use and the spatial allocation defined in the Regional Spatial Plan (RTRW) of South Lampung Regency. Land-use mapping, RTRW extraction, and spatial overlay were conducted using QGIS, complemented by field observations of evacuation routes, signage, assembly points, and coastal protection structures. Results indicate that 74.77% (3,998.50 ha) of land use aligns with RTRW, while 25.23% (1,349.38 ha) shows nonconformity, mainly due to changes in agricultural and forest areas. In terms of tsunami mitigation, Rajabasa has breakwaters, evacuation paths, and temporary assembly points; however, the distribution remains uneven and no vertical evacuation shelters exist. A 1,300-meter buffer analysis reveals that several settlements lie outside effective evacuation coverage. All analytical outputs were integrated into an interactive WebGIS platform developed using QGIS, qgis2web, GitHub, and Netlify. This platform enhances data transparency and supports evidence-based decision-making related to land suitability, hazard exposure, and mitigation infrastructure. The study concludes that strengthening spatial-plan enforcement, improving mitigation facilities, and enhancing community preparedness are essential for building coastal resilience aligned with disaster risk reduction principles and the Sustainable Development Goals.